Characterization of starches obtained from several native potato varieties grown in Cusco (Peru) - Martínez P. (2021)
Abstract: Ten native potato varieties grown in Cusco (at 3,672 m above sea level) were used for starches extraction (at a pilot scale), and their physicochemical, functional, morphological, and structural characteristics were assessed. The content of protein, apparent amylose and phosphorus ranged from 0.1% to 0.44%, 23.42% to 35.5%, and 0.07 to 0.10%, respectively. Starch granules revealed smooth surface, with ellipsoidal and spherical shapes, particle size analysis exhibited bimodal or multimodal distribution, while the averaged crystallinity was 27.7% assessed by XRD. Gelatinization temperatures of the starches ranged from 57.4 to 60.1 °C, 60.8 to 64.3 °C, and 68.4 to 71.1°C for To, Tp, and Tc, respectively; and the gelatinization enthalpies ranged from 15.4 to 17.1 J/g. Respect to pasting properties, the peak viscosity and setback viscosity ranged from 12,970 to 16,970 mPa?s and from 968 to 2498 mPa?s, respectively. Thermogravimetric analysis (TGA) revealed no significant relationship between apparent amylose content and thermal stability. Therefore, the results reveal subtle differences in the functional characteristics of the starches from the native varieties of potato studied, which can be recommended for food industry applications. Practical Application: This study contributes to show several varieties of native potatoes from Cusco and their valorization as nonconventional starch source. Describing the physicochemical, functional, and structural characteristics of these starches could be useful for food industry applications. © 2021 Institute of Food Technologists®